Best Practices in Promoting Disability Inclusion Within Canadian Schools of Social Work - Dunn, Peter; Hanes, Roy; Hardie, Susan; Leslie, Donald; MacDonald, Judy (Disability Studies Quarterly, 2008)
The profession of social work has a long history of work with "clients" with disabilities, but unfortunately, this history often has not included strong advocacy for their rights and creating a place as colleagues within Schools of Social Work (Dunn, Hanes and MacDonald, 2003). From a critical disability perspective and a view of disability as being socially constructed, the profession and its educational institutions need to rethink their approach to students, faculty and staff with disabilities (May & Raske, 2005). Best practices in accessibility, accommodation and inclusivity will be explored within Canadian Schools of Social Work. Knowledge shared in this article was derived from a critical review of the literature, a survey of Schools of Social Work in Canada (Dunn, Hanes, Hardie, and MacDonald, 2006), and a National Best Practices conference (Dunn, Hanes, Hardie, Leslie, and MacDonald, J, 2004). Disability inclusion within Schools of Social Work is explored in five main areas: 1) recruitment and admissions; 2) accommodation; 3) curriculum; 4) field placements; and 5) retention, graduation and meaningful employment. While the specific focus is on social work education the principles and practices can be applied to other disciplines within the academy and beyond.